The Joint Mobile Emerging Disease Clinical Capability (JMEDICC) laboratory approach: Capabilities for high-consequence pathogen clinical research. - Prossy Naluyima; Willy Kayondo; Chi Ritchie; Joseph Wandege; Sharon Kagabane; Lydia Tumubeere; Brenda Kusiima; Daniel Kibombo; Sharon Atukunda; Christine Nanteza; Harriet Nabirye; Francis Bunjo Mugabi; et al. (Public Library of Science (PLoS), 2019)
Following the 2013-2016 Ebola virus outbreak in West Africa, numerous groups advocated for the importance of executing clinical trials in outbreak settings. The difficulties associated with obtaining reliable data to support regulatory approval of investigational vaccines and therapeutics during that outbreak were a disappointment on a research and product development level, as well as on a humanitarian level. In response to lessons learned from the outbreak, the United States Department of Defense established a multi-institute project called the Joint Mobile Emerging Disease Intervention Clinical Capability (JMEDICC). JMEDICC's primary objective is to establish the technical capability in western Uganda to execute clinical trials during outbreaks of high-consequence pathogens such as the Ebola virus. A critical component of clinical trial execution is the establishment of laboratory operations. Technical, logistical, and political challenges complicate laboratory operations, and these challenges have been mitigated by JMEDICC to enable readiness for laboratory outbreak response operations.